A flexible dry electroencephalogram electrode based on graphene materials. (24th May 2019) - Shao, Li; Guo, Yunfei; Liu, Wenjun; Sun, Tai; Wei, Dapeng
Abstract: In order to realistically collect Electroencephalogram (EEG) signals in complicated environments, low impedance and flexibility are considered as two crucial characteristics for EEG electrode. We designed and manufactured a type of dry EEG electrode based on graphene with matrix micro-pyramid structure on the surface. This EEG electrode could not only reduce the contact impedance, but also improve the stability of the electrode. Furthermore, based on these flexible graphene EEG electrodes, we assembled a system that could monitor human EEG signals in real time. When a tested person was answering the phone or driving while tired, the system could give him appropriate warnings, so as to reduce the occurrence of accidents. This brain-computer interface system was wearable and suitable for intelligent detection of EEG signals.